2015
DOI: 10.1007/s10653-015-9755-3
|View full text |Cite
|
Sign up to set email alerts
|

Hair elements and healthy aging: a cross-sectional study in Hainan Island, China

Abstract: Healthy aging is considered as the core issue of aging population. Centenarians are a symbol of healthy aging. Concentration of elements in hair is an indicator of micronutrient status, which can affect the human health. In the present study, we investigated element concentrations in the scalp hair of 255 healthy centenarians from Hainan Island, China. The pattern of intergenerational transmission of elements and the effects of confounders such as sex, age, education level, smoking habits, alcohol intake, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Se is an essential trace element to humans, and average Se contents in the body decrease with increasing age. Se in hair decreased significantly through intergenerational transmission (grandchildren > children > centenarians) [ 26 ], which means Se supplementation is important for healthy aging. In this paper, the correlation coefficient of Se with the longevity ratio is not as high as temperature and humidity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Se is an essential trace element to humans, and average Se contents in the body decrease with increasing age. Se in hair decreased significantly through intergenerational transmission (grandchildren > children > centenarians) [ 26 ], which means Se supplementation is important for healthy aging. In this paper, the correlation coefficient of Se with the longevity ratio is not as high as temperature and humidity.…”
Section: Discussionmentioning
confidence: 99%
“…This is because Se varied largely even at a small scale in soil, high Se content and low Se content usually coexist in a city, and the research scale of this paper is still too large to show relationship between Se and longevity. Some studies at the town scale and county scale within a city have shown that climate factors is almost the same, so Se will be more significant related to longevity [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group’s follow-up study on 78 centenarians suggests that regulating in vivo contents of trace elements, especially Se, Co, and Zn, is a reasonable approach to intervene with geriatric diseases (Li et al 2012). Based on a sample of 255 centenarians and their 124 children and grandchildren, the group led by Wang and Li found that adequate concentrations of Fe and Se might increase the life span of centenarians, whereas excessive concentrations of P and Pb were harmful to health and may reduce life span (Hao et al 2016). …”
Section: Phenotypic Health Characteristicsmentioning
confidence: 99%
“…Individuals with a family record of neurodegenerative conditions (ANT1) are mainly associated to a diagnosis of "normal" (MMS1-MCI, MOC2-normal, CDR0-normal, dia 0-normal) and low levels (category 1) of PTEs in urine. Although recent studies investigating relationships between PTEs levels in toenail clippings or human hair and socio-economic factors are available from the literature (Cabral Pinto et al 2013;Ndilila et al 2014;Cabral Pinto et al 2015;Hao et al 2015;Reis et al 2015), to the best of our knowledge this has not yet been attempted using urine samples as specimen to measure biomarkers of environmental exposure and its impact on the health status of the population.…”
Section: Relationships Between Social-behavioral Factors Cognitive Tmentioning
confidence: 99%